9 - Effets de la Covid-19 sur les entreprises du secteur informel agricole au Sénégal - Sidia Diaouma Badiane; Amadou Tandjigora; Thierno Bachir Sy; Adjani Nourou-Dine Yessoufou; Mamoudou Dème (Africa Development, 2023)
This article focuses on the effect of the COVID-19 crisis on informal enterprises in the Senegalese agricultural sector. The methodological approach adopted combines a documentary review and descriptive analyzes with the support of data from the survey on “Monitoring of the impact of COVID-19 on informal sector units 2020”, from the National Agency for Statistics and Demography (ANSD). The results of the analysis made it possible to inform the main channels through which the pandemic affected the IPU. It appears that the restrictions linked to the pandemic are mainly the cause of the permanent or temporary closure of the units. Added to this are the difficulties in the supply of raw materials and the sale of products. This negatively affects the turnover of these entrepreneurs. This situation translates into a drop in production of at least 25 per cent for 95.1 per cent of respondents. Consequently, the downward variation of personnel, exclusively men, is noted for 10 per cent of the IPU. It manifests itself in part through the adoption of coping strategies to cope with the effects of the crisis. In this wake, product diversification was a healthy approach for 46.5 per cent of units.